Enhanced MPR selection strategy for multicast OLSR - Matter, Safaa S.; Shaikhli, Imad F. Al; Hassan Abdalla Hashim, Aisha; Ahmed, Abdelmoty M.; Khattab, Mahmoud M. (IJCSNS, 2022)
Wireless community networks (WCNs) are considered another form of ownership of internet protocol (IP) networks, where community members manage and own every piece of equipment in a decentralized way, and routing for traffic is done in a cooperative manner. However, the current routing protocols for WCNs suffer from stability and scalability issues. In this paper, an enhanced routing protocol is proposed based on the optimized link state routing (OLSR) protocol to meet the standards of efficiency in terms of stability and scalability. The proposed routing protocol is enhanced through two phases: multicasting expansion and multipoint relay (MPR) selection based on an analytical hierarchical process (AHP). The experimental results demonstrate that the proposed routing protocol outperforms the OLSR protocol in terms of network control overhead and packet delivery ratio by 18% and 1% respectively.